The Influence of CEO Characteristics on Environmental, Social, and Governance (ESG) Information Disclosure at IDXESGL - Sholeha Kurnia Difitri; Indah Oktari Wijayanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The objective of this research is to examine how the traits of CEOs impact the release of ESG information in companies that are part of the IDXESGL index on the Indonesian Efe Exchange (IDX) during the timeframe of 2021-2023. The characteristics of the CEOs studied are with four characteristics including tenure, age, gender, and educational background. The findings of the study revealed that the tenure and age of the CEO had a negative effect on the disclosure of ESG information, while the gender and educational background of the CEO had a positive influence on the disclosure of ESG information. This study only considers four characteristics of CEOs as independent variables that affect the disclosure of ESG information so for future researchers it is suggested to add other factors of CEO characteristics such as citizenship & ethnicity, and CEO narcissism so that they can be explained simultaneously in the research model to obtain a more thorough understanding of the influence of CEO characteristics on ESG information disclosure. These results will offer useful perspectives on how the traits of a CEO can impact the choices and behaviors they make in relation to ESG. These findings can also contribute to corporate governance literature and provide practical implications for companies in formulating effective ESG information disclosure strategies for a company's sustainability.